Developing an automatic handwashing innovation for Thai preschool children - Chaiyasung, Phatcharaphan; Sritakaew, Nuttaya; Rojanaprasert, Pilailak; Thohinung, Usa; Meesomsak, Nisapichayapak; Triamlumlerd, Sirichai (Intelektual Pustaka Media Utama, 2025)
Handwashing is vital in COVID-19 prevention and other infectious diseases. However, ensuring regular handwashing among children aged 3-5 proves challenging due to inconsistent compliance. This study aimed to develop and evaluate an automatic handwashing innovation for preschools, involving 13 executives from local organizations, a health-promoting hospital, and 77 children aged 3-5 from Khlong 6, Pathum Thani, Thailand. Evaluation tools included in-depth interview questionnaires, an automatic handwashing evaluation form, and preschool behavior assessment tools. Data collection methods included in-depth interviews and experimental group evaluations, with analysis involving content analysis, mean, and standard deviations. Findings indicated that: i) Caregivers struggle to consistently supervise children's handwashing, particularly before meals, after bathroom use, and when touching public surfaces; ii) The automatic handwashing innovation effectively caters to the community's needs in early childhood care; and iii) The design of this innovation should prioritize elements that enhance children's enjoyment and safety. The final prototype is a screen-based system that demonstrates automated handwashing. It features a bear character who guides the handwashing techniques and music for three minutes. Post implementation, preschoolers demonstrated improved independent handwashing skills, achieving high scores (X=1.87, SD=0.212). Future advancements in this area should continue focusing on child-centric design to promote early childhood hand hygiene effectively.